(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Hypertension during pregnancy is one of major causes in our country (Iraq), and at AL – Ramadi city (PHCCs) for morbidity in pregnant women. Several risk factors have been studied to show the impact on induced hypertension during pregnancy.Objectives: TO find out associations between certain risk factors and their effects on pregnancy induced hypertension in PHCCs.Materials and Methods: A cross-sectional study in two main PHCCs was conducted In First sector in AL-Ramadi city. (AL-ANDULUS), and (AL-TASH) PHCCs which represent urban and rural area respectively .the data was collected from March through September- 2022 in PHCCs. Questionnaire was designed for purpose of study. Both cases and controls were examined for hypertension. The cases (170) hypertension women, were diagnosed by examination and information of pregnant women and repeated measurement of blood pressure, and (210) healthy pregnant women. Analysis by chi – square test, p-value less than (0.05) were significant association.Results: The present study shows that significant association between risk factors and hypertension during pregnancy a include maternal age , level of education parity, BMI , family history , smoking during pregnancy , previous type of delivery, previous history of PIH, spacing , ,Contraception more association in use pills, .Conclusion: The study shows that there was significant association between the following risk factors and PIH. Age of pregnant hypertensive women, education level more in low education level . Parity more ≥5,BMI, positive Family history, Smoking, Elective C/S, Previous history PIH .Spacing 2-3 years interval .Use of contraception more in pills users.